166k views
4 votes
If JM = 5x - 6 and LM = 2x - 6 , which expression represents JL ?

User Dheepak
by
4.7k points

2 Answers

2 votes

Answer:

3x - 2

Step-by-step explanation:

If JM = 5x -8 and LM = 2x -6, 3x -2 represents JL

If JM = 5x - 6 and LM = 2x - 6 , which expression represents JL ?-example-1
User Daniel Tranca
by
4.4k points
7 votes

Given:

JM = 5x-6

LM = 2x-6

To determine:

the expression for JL

Step-by-step explanation:

JL = JM - LM = 5x-6 -(2x-6) = 3x

Ans: JL = 3x

User CiucaS
by
5.4k points